2003
DOI: 10.1103/physrevlett.91.072305
|View full text |Cite
|
Sign up to set email alerts
|

Transverse-Momentum Spectra inAu+Auandd+AuCollisions at

Abstract: We present spectra of charged hadrons from Au+Au and d+Au collisions at sqrt[s(NN)]=200 GeV measured with the BRAHMS experiment at RHIC. The spectra for different collision centralities are compared to spectra from p+(-)p collisions at the same energy scaled by the number of binary collisions. The resulting ratios (nuclear modification factors) for central Au+Au collisions at eta=0 and eta=2.2 evidence a strong suppression in the high p(T) region (>2 GeV/c). In contrast, the d+Au nuclear modification factor (a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
38
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 307 publications
(43 citation statements)
references
References 33 publications
5
38
0
Order By: Relevance
“…Þ is not that of a standard Wilson loop-the operators (like the color matrices) are path ordered, whereas in a standard Wilson loop operators are time ordered. This subtlety, which had not been noticed 1 Throughout this paper, k ? is the two-dimensional vectork ?…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Þ is not that of a standard Wilson loop-the operators (like the color matrices) are path ordered, whereas in a standard Wilson loop operators are time ordered. This subtlety, which had not been noticed 1 Throughout this paper, k ? is the two-dimensional vectork ?…”
Section: Introductionmentioning
confidence: 62%
“…One of the central discoveries made in experimental heavy ion collisions at the Relativistic Heavy Ion Collider (RHIC) at Brookhaven National Laboratory is that the droplets of quark-gluon plasma produced in these collisions are sufficiently strongly coupled that they are able to ''quench jets'' [1][2][3][4]. That is, when a very energetic quark or gluon (energetic enough that if it were in vacuum it would manifest itself as a jet, and with an energy that is much greater than the temperature of the medium in which it finds itself) plows through the strongly coupled plasma, it loses sufficient energy that few high momentum hadrons are seen in the final state.…”
Section: Introductionmentioning
confidence: 99%
“…In heavy ion collisions, scattering processes with large momentum transfer Q (of order 100 GeV or more) between the partonic constituents of the colliding nuclei occur early. Energy loss experienced by these high-momentum partons (quarks or gluons) as a result of their interactions with the colored, hot and dense quantum chromodynamics (QCD) medium created in heavy ion collisions (the quark-gluon plasma, or QGP) [1,2], was first observed at BNL RHIC [3][4][5][6] and then at the CERN LHC [7][8][9]. Interactions of the outgoing partons with the QGP are also expected to modify the angular and momentum distributions of the parton shower relative to proton-proton (pp) collisions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was found that jetlike correlations opposite to trigger jets are suppressed and that the azimuthal anisotropy in hadron emission persists out to very high p T [2][3][4]. In contrast, no suppression effects were seen in d + Au collisions [5][6][7][8], which has led to the conclusion that the observations made in Au + Au are attributable to the high-density medium produced in such collisions and not to initial-state effects. The most probable explanation to date is that the suppression is attributable to parton energy loss from induced gluon radiation (jet quenching) in the extremely hot and dense medium [9].…”
Section: Introductionmentioning
confidence: 99%